Effect of Reformation of the Anterior Chamber by Air or by a Balanced Salt Solution (BSS) on Corneal Endothelium after Phacoemulsification: A Comparative Study - Alahmady Hamad Alsmman; Mohammed Ezzeldawla; Amr Mounir; Ashraf Mostafa Elhawary; Osama Ali Mohammed; Mahmoud Farouk; Ahmed Mohamed Sherif (Journal of Ophthalmology)
Aim. To study the effect of reformation of the anterior chamber by air or by a balanced salt solution, after smooth phacoemulsification on the corneal endothelial count and morphology. Methods. A prospective interventional nonrandomized comparative study included 500 eyes of 500 patients with age range between 50 and 60 years, prepared for cataract surgery and presented to the Ophthalmology department of Sohag University Hospital in the period from October 2016 to May 2017. Corneal endothelial morphology and count were examined, and the results were recorded for all cases before the surgery. Patients were divided into two groups, and both groups were diagnosed with grade 2 cataract and underwent uncomplicated phacoemulsification performed by well-trained surgeons. At the end of the surgery, group 1 was subjected to a reformation of the anterior chamber via a balanced salt solution (BSS) injection while group 2 was subjected to a reformation of the anterior chamber via air injection. Corneal endothelial morphology and count were evaluated in the first and 3rd month postoperatively. Results. The study included 500 patients (250 in each group), 220 males (44%) and 280 females (56%) with no significant statistical age differences. Both preoperative and postoperative (3 months after the operation) recorded parameters of the corneal endothelium did not show any significant statistical differences. The cumulative dissipated energy was recorded, for all cases of both groups, during phacoemulsification with no significant statistical differences (P=0.7). Conclusion. There is no difference between the effect of reformation of the anterior chamber after phacoemulsification, using air or using a BSS injection, on the corneal endothelial count and morphology.